THE CHARISMA OF KIAI IN POLITICS: THE STUDY OF THE KIAI’S BOOK “KIAI DI TENGAH PUSARAN POLITIK ANTARA PETAKA DAN KUASA” BY IBNU HAJAR'S WORKS - Moh. Romdhan; Abdul Wahid (INNOVATIO: Journal for Religious Innovations Studies, 2023)
My research background is motivated by the existence of a charismatic figure (Kiai) who dared himself to enter politics. In the existing reality, Kiai is a figure known to the public as the nation's education generator, not as a politician who is commonly known as a liar who often campaigns for promises without proof. This study aims to formulate a definition of politics, politics according to an Islamic perspective, and the charisma of Kiai in politics. The results of this research describe the figure of a charismatic Kiai who dared himself to enter into politics, where the decision will give birth to a big challenge, so he is in a dilemma with two choices, namely disaster with his decision or gaining power. The Kiai-politician has two important roles, apart from being a generator of education; besides that, he is also a politician who can be seduced by wealth and power. This reality requires Kiai not to be proactive; it is enough for him to become a driving force behind the curtain, without taking part in politics. Thus, the Kiai will be safe from all kinds of slander and accusations that can corner him so that he will not lose his dignity and charisma, and society will always make him 'uswatun hasanah', which will be kept in their chest all the time. Abstrak: Peneitian kami ini dilator belakangi dengan adanya sosok kharismatik (kiai) yang memberanikan dirinya untuk terjun ke dalam dunia pokitik. Dalam realita yang ada, kiai adalah sosok yang dikenal masyarakat sebagai generator pendidkan bangsa, bukan sebagai politikus yang jamak dikenal sebagai seorang pendusta yang kerap mengkapanyekan janji tanpa bukti. Penelitian ini bertujuan untuk merumuskan definisi politik, politik menurut perspektif Islam, dan kharisma kiai dalam dunia politik. Hasil penilitian ini menggambarkan tentang sosok kiai kharismatik yang memberanikan dirinya untuk terjun ke dalam dunia politik praktis, di mana keputusan tersebut akan melahirkan tantangan besar, sehingga ia dilema dengan dua pilihan, yakni petaka dengan keputusannya atau justru mengapai kuasa. Kiai-politikus memiliki dua perananan penting, selain sebagai generator pendidikan, di samping itu ia juga sebagai sosok politikus yang dapat tergoda oleh harta dan kekuasaan. Realita tersebut, menuntut kiai untuk tidak ikut pro-aktif, cukup ia menjadi mesin penggerak di balik tirai, tanpa ikut berenang dalam dunia politik. Dengan demikian kiai akan selamat dari segala macam fitnah dan tudingan yang dapat menyudutkan dirinya, sehingga ia tidak akan kehilangan marwah dan kharismanya dan masyarakat akan senantiasa menjadikannyha uswatun hasanah yang akan terpelihara di dada mereka sepanjang masa. Kata kunci : kharisma, kiai, politik.